2016
DOI: 10.1111/jfq.12200
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Dark Chocolate Produced from Vietnamese Cocoa Liquors

Abstract: This study provides the quality aspects of Vietnamese (VN) dark chocolates produced by cocoa liquors exhibiting different degrees of acidity. Hereto, the impact of preconching the highly acidic cocoa liquors was investigated. Results show that three out of four VN chocolates attained comparable solid fat content at 35C, particle sizes and flow properties to a Ghanaian reference, ensuring a similar volatile release and taste perception. Principal component analysis of the aroma compounds obtained using headspac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Similarly, for a type of cacao butter from Ghana, Tran et al 25 report a SFC of 85.90% ± 0.20% at 10°C, 74.60% ± 0.20% at 20°C, 65.30% ± 0.30% at 25°C, 40.30% ± 0.50% at 30°C and 0.70% ± 0.20% at 35°C, which are similar to the results of the present study at temperatures of <20°C. However, at temperatures of 25°C, the SFC was higher in our study, confirming the heat resistance of cacao butter.…”
Section: The Proximal Chemical Composition Of Cacao Beanssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, for a type of cacao butter from Ghana, Tran et al 25 report a SFC of 85.90% ± 0.20% at 10°C, 74.60% ± 0.20% at 20°C, 65.30% ± 0.30% at 25°C, 40.30% ± 0.50% at 30°C and 0.70% ± 0.20% at 35°C, which are similar to the results of the present study at temperatures of <20°C. However, at temperatures of 25°C, the SFC was higher in our study, confirming the heat resistance of cacao butter.…”
Section: The Proximal Chemical Composition Of Cacao Beanssupporting
confidence: 91%
“…However, at temperatures of 25°C, the SFC was higher in our study, confirming the heat resistance of cacao butter. In the ΔS experiment, the SFC values in CCN 51, ICS 6 and the "optimal chocolate" were 65.01%, 65.52% and 65.34%, respectively, which were within the study range reported by Tran et al25 In the last section of the SFC curve (temperatures of 35°C-40°C), the butter in the present study had waxy residues, more than that of the varieties from Vietnam and Ghana 25 .…”
Section: The Proximal Chemical Composition Of Cacao Beanssupporting
confidence: 85%
“…The last processing step relevant with respect to flavor is conching, which significantly contributes to the formation of the final chocolate flavor. In addition, residual volatile acids such as acetic acid, alcohols (e.g., linalool and 2-phenylethanol), and other off-flavors (e.g., ketones and aldehydes) are removed [1,3,4,11].…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds (VC) profile (volatile acids, alcohols, aldehydes, esters, ketones, pyrazines, furans, among others) of the dark-chocolate samples was evaluated in order to identify possible key aroma markers associated with the different chocolate samples, prepared from the different cacao mass, as well as to evaluate which VC has the strongest correlations with overall acceptability and emotions induced for consumers ( Supplementary Table S3 ). It was reported that several VC of the chocolate aroma are formed as a result of the technological processes [ 16 , 50 ]. However, the short-chain carboxylic acid, acetic acid, was the main VC identified in all the analysed chocolate samples, with the highest percentage in S4, and the lowest in S2 samples (78.23 and 67.90%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In S1 samples, despite a common VC identified in other samples, the main typical VC were 2,3-butanediol, [S-(R*, R*)], which odor is described as fruity and rum-like (2.60%); butanoic acid, 3-methyl-, whose odor is described as rancid and cheesy (0.41%); 2-heptanol (0.48%), which is associated with mushroom odor; sulfurous acid, isobuthyl 2-pentyl ester (0.62%), whose odor is described as orange juicy, impacting, musty green, unripe, fruity, reminiscent of banana and vegetative nuances with a slight nutty note; nonanal (0.40%), which odor is described as waxy, aldehydic, citrus, with a fresh slightly green lemon peel like nuance, and a cucumber fattiness, and other VC in lower percentages. Further, 2,3-Butanediol is eligible VC in high-quality cocoa products because it has a good stability during the production of chocolate [ 20 , 50 ].…”
Section: Resultsmentioning
confidence: 99%